PHENOMENOLOGY APPROACH TO ARABIC LANGUAGE TEACHING - Lubis, Maesaroh; Widiawati, Nani (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This study seeks to understand the underlying meaning of human behavior with complex social settings and interactions. This character is attuned to the complexity of human nature and therefore cannot be explained through preconstructed epistmological assumptions and predictions. As part of the social science tradition, research in Arabic Language Education also leads to this goal. The problems of the Arabic teaching process can be interpreted as the world of life that is lived by teachers and students and becomes the basis for communication actions amongst them. Based on the phenomenological perspective, the act of communication is basically a process of sharing personal experiences. This paper describes phenomenology as a philosophical thought which then shifts into an epistemological mode to construct objective knowledge that is specifically applied in the case of teaching Arabic.Keywords: phenomena, intentionality, teaching Arabic